IMPLEMENTING FLIPPED CLASSROOM TO IMPROVE READING SKILL - Khairani, Mustika; Sutapa, Yohanes Gatot; Regina, Regina (TELL - US JOURNAL, 2024)
This research aimed to find out how the implementation of Flipped Classroom (FC) approach improved reading skills of year-10 students at SMAN 9 Pontianak in the academic year 2022/2023. Classroom Action Research was conducted in two cycles to achieve this goal. The subject of this research was 36 students in class X MIA 2. The researcher used students’ ClassDojo behavior reports, field notes, and reading assignments from ReadWorks as tools to collect the data. The result showed that the implementation of FC improved students’ reading skill. The ClassDojo behavior reports and field notes revealed noticeable changes in both students' behavior during the process FC implementation. These alterations appeared to enhance student motivation and engagement, leading to improved reading comprehension. In addition, results from the reading assignments activities such as rate the word, word builder and an inferring question set from ReadWorks indicated that students had improved their ability to identify the main ideas and their vocabulary within report texts. These outcomes suggest that the activities in FC have potential as a strategy to enhance reading skills among Year 10 students. Therefore, the researcher recommends that teachers employ the FC strategy to help students improve their reading skills. .